2007
DOI: 10.1111/j.1365-246x.2007.03465.x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional radial anisotropic structure of the North American upper mantle from inversion of surface waveform data

Abstract: S U M M A R YSeismic anisotropy provides insight into palaeo and recent deformation processes and, therefore, mantle dynamics. In a first step towards a model for the North American upper mantle with anisotropy characterized by a symmetry axis of arbitrary orientation, aimed at filling the gap between global tomography and SKS splitting studies, we inverted long period waveform data simultaneously for perturbations in the isotropic S-velocity structure and the anisotropic, in the framework of normal mode asymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 91 publications
(135 reference statements)
6
64
0
Order By: Relevance
“…Lebedev et al, 2009). Radial anisotropy in lithospheric mantle across North America (Marone et al, 2007;Nettles and Dziewoński, 2008;Yuan et al, 2011), Australia (Debayle and Kennett, 2000;Fichtner et al, 2010), Africa (Saltzer, 2002;Sebai et al, 2006) and globally (Lebedev et al, 2009;Nettles and Dziewoński, 2008) generally shows faster horizontal wavespeeds than vertical wavespeeds (V SV < V SH ) with a magnitude that decreases with depth from the Moho. However, the magnitude of the anisotropy is generally <4% (Lebedev et al, 2009;Nettles and Dziewoński, 2008), which is too small to account for the MLD phase.…”
Section: Anisotropic Causementioning
confidence: 97%
“…Lebedev et al, 2009). Radial anisotropy in lithospheric mantle across North America (Marone et al, 2007;Nettles and Dziewoński, 2008;Yuan et al, 2011), Australia (Debayle and Kennett, 2000;Fichtner et al, 2010), Africa (Saltzer, 2002;Sebai et al, 2006) and globally (Lebedev et al, 2009;Nettles and Dziewoński, 2008) generally shows faster horizontal wavespeeds than vertical wavespeeds (V SV < V SH ) with a magnitude that decreases with depth from the Moho. However, the magnitude of the anisotropy is generally <4% (Lebedev et al, 2009;Nettles and Dziewoński, 2008), which is too small to account for the MLD phase.…”
Section: Anisotropic Causementioning
confidence: 97%
“…Panning and Romanowicz [2006] also found a strong v SH > v SV anomaly in the Pacific at 150 km, which, in contrast to the results of Ekström and Dziewonski [1998], does not change significantly at shallower depths. Gung et al [2003] reported a strong v SH > v SV trend not only in the suboceanic mantle but also beneath the continental lithosphere, and Marone et al [2007] also found lateral variations in anisotropy under the North America. Significant anisotropic variations within continental plates were observed by Nettles and Dziewoński [2008].…”
Section: Introductionmentioning
confidence: 99%
“…The single-station method has been primarily used to constrain the large-scale S-wave structure (e.g. van der Lee & Nolet 1997;Godey et al 2003;Marone et al 2007;Nettles & Dziewonski 2008), employing permanent global networks and local stations in the United States. The deployment of the Transportable Array (TA; USArray) in the last decade provides us with high-quality broad-band seismic waveform data, which have facilitated a variety of tomographic studies in this region; for example, ambient noise tomography (e.g.…”
Section: Introductionmentioning
confidence: 99%